Identification of carriers of Duchenne/Becker muscular dystrophy by a novel method based on detection of junction fragments in the dystrophin gene. Issue 12 (December 1996) - Yamagishi, H; Kato, S; Hiraishi, Y; Ishihara, T; Hata, J; Matsuo, N; Takano, T
Abstract : We developed a Southern blotting based method that uses rare cutting restriction endonucleases and electrophoresis of single stranded DNA to detect junction fragments resulting from the rearranged dystrophin gene. By conventional Southern blot hybridisation, no junction fragments were detected in 27 unrelated patients with Duchenne (DMD) or Becker (BMD) muscular dystrophy, who had 20 deletions and seven duplications in the dystrophin gene. With our new method, junction fragments were detected in 21 of these 27 patients. When the junction fragments were used as markers, five carriers were unequivocally diagnosed among six females from two families of DMD/ BMD patients. This novel method allows simple and definitive identification of carriers with risk factors for DMD/BMD without using quantitative Southern blot hybridisation.